Caffeine vehiculation into alpha-zirconium phosphate: a multifunctional intercalation product and its application for modified topical release. Issue 4 (27th January 2021) - Bastianini, M.; Sisani, M.; Petracci, A.; Di Guida, I.; Faffa, C.; Cardellini, F.
Abstract : Zirconium phosphate is able to intercalate basic molecules and it is an effective drug carrier that can be used to project slow release for topical applications. Abstract : Caffeine possesses many important biological effects and is known to be a model drug for topical applications. Zirconium phosphate (ZrP) is able to intercalate basic molecules and it is an effective drug carrier. The vehiculation of drugs in lamellar solids can finely tune their properties: in this article the first intercalation of caffeine in ZrP is reported. The intercalation strategy was designed on the basis of the chemical properties of the host and guest, and the synthesized product was fully chemically–physically characterized and tested for topical release using the Franz cell diffusion system.